Complex inferiorities - Matzner, Sebastian,Harrison, Stephen (Oxford University Press, 2018)
The deliberate adoption of a 'weaker' voice by a speaker not obliged to do so is a widespread phenomenon in Latin literature. This volume traces this strategy across a range of genres, periods, and authors, exploring how it establishes, perpetuates, and challenges hierarchies and values in very different literary and cultural-political contexts.
10.1093/oso/9780198814061.001.0001
Keywords: Latein; Literatur; Rhetorik; Unterwürfigkeit; Schwäche